Integrated Risk Management and Its Impact on Financial Performance in Nepalese Commercial Banks (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates the characteristics and relationships of risk factors—credit risk, operational risk, market risk, and non-performing loans (NPLs)—with financial performance metrics, specifically return on assets (ROA) and return on equity (ROE). It further examines the impact of these risks on the financial performance of Nepalese commercial banks. Using a descriptive and causal-comparative research design, the study analyzes secondary data from fiscal years 2012–13 to 2022–23, covering 19 commercial Rastriya Banijya Bank was excluded due to its absence from the stock market. Analytical tools such as descriptive statistics, correlation, and regression analysis were applied.The results indicate that ROE is more variable than ROA, and operational and market risks show greater dispersion compared to credit risk and NPLs. A low degree of positive relationship exists between most risk factors and performance metrics. Notably, NPLs negatively affect financial performance, while credit risk has a positive impact. The study recommends reducing NPLs and managing credit risk within acceptable limits to improve performance. These findings offer valuable insights into the influence of risk factors on bank performance and provide practical implications for financial institutions in emerging markets.